Nutritional periodization: Applications for the strength athlete - Mota, J. A.; Nuckols, G.; Smith-Ryan, A. E. (Strength and Conditioning Journal, 2019)
Nutritional periodization is defined as the preplanned and strategic use of nutritional interventions in efforts to optimize exercise performance and body composition throughout the training program of athletes. Owing to the novelty of the body of literature surrounding nutritional periodization, the direct application of this idea to strength or power athletes has yet to be thoroughly discussed. The purpose of this review is to synthesize the available literature regarding nutritional strategies that may aid the performance of strength and power athletes and discuss how these nutritional strategies can be periodized and integrated into the athlete's preprogrammed training plan.